Dynamics of the Hantavirus infection through variational iteration method - Goh S.M.; Ismail A.I.M.; Noorani M.S.M.; Hashim I. (2023)
This paper studies the dynamics of the Hantavirus infection model, which was originally developed by Abramson and Kenkre [G. Abramson, V.M. Kenkre, Spatiotemporal patterns in the hantavirus infection, Phys. Rev. E 66 (2002) 011912], by using a simple analytical method called the variational iteration method or VIM. The results obtained by the variational iteration method are compared with the classical Runge-Kutta method (fourth-order) to gauge its effectiveness. Numerical values from these analyses provide us with some useful observation on the behaviour of the infection subjected to certain conditions. 2008 Elsevier Ltd. All rights reserved.